Competing paradigms for explaining the etiology of human male homosexual orientation: a case study in the application of the methodology of scientific research programs - Mbûgua, Karori (Department of Philosophy, 2024)
[pg 41,59-61,71,99,110 ,172,173 missing] This thesis is a case study in the application of the principles of the methodology of scientific research programs to a contemporary scientific debate: the debate concerning the causes and origins of human male homosexual orientation. It begins by identifying two major research programs that seek to explain homosexual phenomenon, namely, the biological and experiential research programs. Using the methodology of research programs as a framework for analysis, the study shows that the two programs have stagnated. Neither of them meets the Lakatosian criterion of 'progressivity'. The study argues that lack of progress in this area may be a consequence of the two groups of researchers, the biologists and the experientialists, rigidly clinging to the hard cores of their respective programs. The study calls for an interactionist approach to the study of homosexual etiology and suggests that such an approach could benefit from recent trends in developmental systems theory and evolutionary psychology. It is also argued that this episode in the history of science undermines the normative generalizability of Lakatos' account of science.